SILENCE OF WOMEN IN BYZANTIUM BETWEEN THE CANONS LAW AND THE REALITY (Annual of the Faculty of Philosophy in Skopje, 2016)
The subject of our research is the silence of women in the Middle Ages, with special emphasis of the silence of women in Byzantium, or more precisely - how in reality canonical provisions were respected by women and about provisions that women should remain silent in church at the front of man?To be born as a man or women in any society is not just a simple biological fact. It is a biological fact that has social implications. Women constitute a special social group, and the character of that group, which historians have long ignored, has nothing in common with women's “nature". The problem lies in the nature of society and perception of women, so legal and historical sources speak about that from a special aspect -from a male worldview. Man had legal independence and the right to speak in public, but women were either prohibited or allowed with disapproval. Men possessed the power, and according to that, our sources mainly talk about them. It is particularly dijficult to glance beneath the surface of the Middle Ages in order to realize the life of more modest members of the society. Therefore, our attention is focused to information about women from royal families, empresses; how much the provisions for silence were applicable for them and how some of them were engaged in discussions about certain religious issues, and their opinions led to important decisions which had a significant effect to the events in Byzantium. All of Byzantines which kept the data about their civilization (historians, lawyers or hagiographical compilers) were men and their writings are devoted to activities of their male fellows; that fact which make difficulties to our research, so we will refer to the provisions of the Byzantine legislation.
Keywords: WOMEN; LAWS; CANONS; EMPRESSES; RELIGIOUS DEBATES; SILENCE